Implications of Visual Complaints on Student Learning Achievement - Ni Wayan Sadiyani; I Ketut Widana; I Nyoman Sutarna (Politeknik Negeri Bali, 2019)
This research is a study of the effect of visual complaints on learning achievement. High and low visual complaints are strongly influenced by student mobility or motor activity. Mobility can also maintain concentration to be maintained at a certain time. Class mobility is carried out through simple interactive learning, which is an effort to invite students to always move and always be active in the learning process. The long-term goal of research is to obtain effective learning strategies in vocational universities, while the short-term goal of research is to obtain learning methods in English subjects that are best able to provide optimal results on student academic achievement. Departing from the problem that the concentration of students decreases in line with the length of the lecture and the lack of student interaction in the classroom, a strategy is made that allows the concentration of students to be maintained during the lecture process by increasing student mobility in the classroom. To find out the impact of the treatment/ intervention on the subject's condition, a real experiment will be conducted using the two period cross over design. The assessment of the quality of the learning process was carried out with 2 cycles of study, in which each cycle was ended by giving a test/questionnaire. Data were analyzed descriptively qualitatively. Student learning achievements in the form of final grades are calculated according to the grade with the following weighting: 10% daily quiz/test + 10% assignment + 10% report + 30% Middle Semester Exam + 40% Final Semester Examination. The results showed that high visual complaints can reduce concentration and reduce student achievement.